Aza-Michael Addition of 2-Amino Pyridine with 7-Aza-2-Indolone Chalconides: Synthesis of Functionalized α-Enaminones and One-Pot N-Alkenylation-Dearomatization of Pyridine Ring - Preethi, Raman Kavitha; Padmashrija, Ammundi Jayavel Chirranjeevi; Sathananthan, Kannadasan; SHANMUGAM, Ponnusamy (Synlett)
A facile, efficient and catalyst free synthetic route for the synthesis of α-enaminones, a motif found in synthetically and biologically active compounds have been developed by the reaction of 2-amino pyridine with 7-aza-2-indolone chalcone derivatives adopting aza-Michael addition as a key reaction. To demonstrate substrate scope, an array of α-enaminones was synthesized from a number of N-alkylated-3-acylidene-7-aza-2-indolones and aromatic 2-amino azaheterocycles and carbocycles in excellent yield. The structure and relative stereochemistry of representative compounds has been established by the single-crystal XRD. Based on control experiments a plausible and alternate operating mechanism for the formation of the products is also provided. Significantly synthetic transformation of the Aza Michael products thus obtained were successfully demonstrated by unusual heterocyclic functionalization via N-alkenylation and de-aromatization of pyridine ring has also been provided.